Contribution of Area Change to Minangkabau International Airport (BIM) to the Community in Kenagarian Ketaping West Sumatra - Daniati, Nia; Saputri, Fadilla; Permata, Bunga Dinda; Liandra, Febi Dwi; Bhakti, Novran Juliandri (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
Nagari Ketaping, located in Batang Anai District, West Sumatra, has undergone significant land use changes, primarily due to the establishment of Minangkabau International Airport (BIM) in 2005. Initially a swamp and forest area, this region has transformed into a rapidly developing urban area, triggering various socio-economic and cultural shifts. This study aims to analyze the impact of these changes on the local community, including population growth, livelihood transitions, educational access, and social interactions. A qualitative research approach with a descriptive method was employed. Data collection techniques included interviews and observations, involving five key informants: local government representatives, affected residents, and workers. Observations were conducted to examine land use transformation, including the construction of infrastructure such as housing complexes, overpasses, highways, and airport railway connections. The findings reveal that the airport's presence has significantly increased the population due to urbanization and migration. New housing developments have proliferated, attracting settlers from various regions. Economic shifts are evident, with residents transitioning from agricultural livelihoods to employment in trade, construction, and service industries. Additionally, the expansion of educational facilities has improved access to schooling, supporting human resource development. Changes in social interaction patterns are also observed, as denser settlements foster stronger community bonds and reduce crime rates. The study applies Herbert Spencer's evolutionary theory, which posits that societal transformations occur gradually. The development of BIM has triggered continuous infrastructure expansion, leading to sustained regional and socio-economic growth. However, discrepancies remain in employment opportunities for indigenous residents despite prior agreements. The findings highlight the profound influence of large-scale infrastructure projects on local communities, emphasizing the need for inclusive and sustainable development policies.